Primitive Neuroectodermal Tumor of Axilla: A Rare Case Report - Rahul Mahawar; Dorafiona Swer; Laishram Singh (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Primitive neuroectodermal tumors (PNETs) are poorly differentiated small round cell neoplasms. It is commonly seen in children and is rare in adults. Superficial primitive neuroectodermal tumors are rare but have a favorable prognosis compared to conventional deep-seated tumors. PNETs are quite rare, with the incidence of PNET axilla being extremely rare, and very limited cases have been reported due to its rareness in literature. This paper reports a case of a 71-year-old male patient who presented with a right axillary swelling. He underwent wide local excision of axillary swelling, which on histopathological examination showed features consistent with primitive neuroectodermal tumor. He was treated with multimodality treatment. Further, treatment was deferred due to the poor general condition of the patient, and he was kept on the best supportive care.